Heart Failure and Chronic Kidney Disease: Should We Use Spironolactone?. (August 2015) - Agrawal, Sahil; Agrawal, Nikhil; Garg, Jalaj; Mohandas, Rajesh; Gupta, Tanush; Segal, Mark
Abstract : Abstract: Half of all deaths in patients with chronic kidney disease (CKD) arise from cardiovascular causes. Congestive heart failure (CHF) is specifically more frequent with CKD. Cardiovascular therapies with proven benefit are often withheld from patients with renal disease for fear of adverse events. The renin-angiotensin-aldosterone system (RAAS) has been implicated as an important maladaptive neurohormonal pathway in heart failure. Angiotensin-converting enzyme inhibitors and angiotensin receptor blockers have been shown to suppress it ineffectively. Current guidelines support the use of spironolactone for more comprehensive suppression of the RAAS in heart failure patients. Most supporting trials have however excluded patients with renal dysfunction resulting in a dearth of data to support use of spironolactone in CKD patients with CHF. Several small studies that prospectively interrogated the benefits of augmented RAAS blockade with spironolactone in CKD patients have shown improvement in predictors of cardiovascular mortality. More recently, improved mortality outcomes were demonstrated with the use of spironolactone in hemodialysis patients. Although reduction in glomerular filtration rate and hyperkalemia are potential adverse effects with its use, the available evidence suggests that it is uncommon and serious consequences can be avoided with close monitoring. Studies investigating the optimal spironolactone dosage in such a setting recommend starting with a low dose and careful uptitration. This review attempts to provide a comprehensive insight into the issues associated with the use of spironolactone in the setting of concomitant CHF and CKD.